2000
DOI: 10.1063/1.1312867
|View full text |Cite
|
Sign up to set email alerts
|

Two- and N-step correlated models for the analysis of molecular dynamics trajectories of linear molecules in silicalite

Abstract: Recent molecular dynamics data on the diffusion of linear diatomic and triatomic molecules in the zeolite silicalite are analyzed in terms of a new correlated model ͓F. Jousse, S. M. Auerbach, and D. P. Vercauteren, J. Chem. Phys. 112, 1531 ͑2000͔͒ capable to account for both first-and higher-order correlation effects. This ''N-step'' model reproduces very well our calculated mean square displacements and diffusion coefficients of the molecules considered. The improvements with respect to the results obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…This means that a molecule passing a channel intersection continues on its way independent of its past (i.e., independent of the channel intersection from where it has come). Although in numerous experimental , and simulation studies eq 1 was found to serve as a reasonable estimate, in several cases the deviations were found to be physically significant.
1 Topology of the channels in silicalite-1.
…”
Section: Introductionmentioning
confidence: 96%
“…This means that a molecule passing a channel intersection continues on its way independent of its past (i.e., independent of the channel intersection from where it has come). Although in numerous experimental , and simulation studies eq 1 was found to serve as a reasonable estimate, in several cases the deviations were found to be physically significant.
1 Topology of the channels in silicalite-1.
…”
Section: Introductionmentioning
confidence: 96%
“…In numerous experimental [127,185] and simulation studies [139,172,176,[180][181][182]186], (171) has in principle been confirmed, although some deviations have also been observed. In [139] these deviations were quantified by introducing a memory parameter…”
Section: Diffusion Memory Of Methane In Silicalite-1mentioning
confidence: 59%
“…silicalite. The black dots show the intersections between straight channels and zigzag channels in the unit cell and the grey dots show intersections of the straight channels with zigzag channels that are outside the unit cell diffusion [180][181][182]. If such effects are neglected, the principal values of the diffusion tensor, i.e.…”
Section: Diffusion Memory Of Methane In Silicalite-1mentioning
confidence: 98%
“…There is no need anymore for including the correlation of subsequent displacements by introducing memory parameters. [16][17][18][19][20][21] This simplification, however, doesn't allow anymore the prediction of structurerelated diffusion anisotropy, as the prevailing feature of the original model presented in ref. 7.…”
Section: Discussionmentioning
confidence: 99%
“…In the extreme case of hardly any interchange the molecules essentially remain in one channel, so that D z approaches zero and b ) 1. Several papers [16][17][18][19][20][21] deal with the possibilities to account for correlations between subsequent dispacements and to derive the corresponding relations for the memory parameter b and, thus, for the interrelation of the principal elements D i of the diffusion tensor. In this paper (section 2) we develop a model for diffusion in MFI-type zeolites where the channel segments, i.e.…”
Section: Introductionmentioning
confidence: 99%